Does the undergraduate experiential learning programme in paediatrics adequately prepare students for work place? Perceptions of community service physiotherapists - Sibuyi, Makwena Midah (My University, 2017)
Background: Universities are expected to produce quality graduates that will be capable of addressing the health care needs of their surrounding community. Since the inception of compulsory community service in South Africa, the experiences of physiotherapists in their community service year have been investigated, and amongst other findings, it was reported that certain skills were not covered sufficiently during their undergraduate training. However, undergraduate paediatric experiential learning programmes have not been studied. Thus, research in this field is scarce. Aim: This study aimed to determine whether community service physiotherapists perceived the undergraduate experiential learning programmes in paediatrics to have adequately prepared them for employment and furthermore to determine the contributing factors that lead to the perception of adequate preparedness. Methods: A total of 250 community service physiotherapists in the year 2015 were invited to take part in the study via text messages and emails. Of these, only 101 responded and agreed to take part in the study. A link to the self-constructed online questionnaire with RedCap was emailed to the participants. The participants were informed that participation in the study implied consent. An email reminder was sent every seven days for a period of three months to participants who had not completed and submitted their questionnaire. All data from the completed questionnaires was analysed on the RedCap account by the researcher. Quantitative data was analysed with a statistical test, STATA version 9.0, and a p-value of less than 0.05 was considered statistically significant. Results: Only one questionnaire was disqualified from the 101 questionnaires that were received. Therefore, the study achieved a response rate of 40%. Overall, 57% of the community service physiotherapists felt adequately prepared to render paediatric services at their workplace. Graduates that had a specific paediatric block felt more prepared than those who did not have a specific paediatric block. The university from which community service physiotherapists have graduated contributed significantly to the perception of adequate preparedness. Conclusion: This study identified the need to develop comprehensive guidelines for the undergraduate paediatric programmes and to develop a standardised paediatric physiotherapy framework for the eight institutions in South Africa. Universities without a structured paediatric block should consider implementing such a block in order to enhance their students‟ experience and confidence. Keywords: curricula review, paediatric physiotherapy, communication, clinical competence, clinical education
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science (Physiotherapy) Johannesburg, 2017.
Keywords: Pediatrics; Problem-Based Learning (Experimental Learning); Community Health Services